STRATEGI PENINGKATAN MUTU LAYANAN ADMINISTRASI DALAM MEMBANGUN RESPONSIVENESS TENAGA ADMINISTRASI DI SMK AL FUDHOLA BEKASI - Pebriani, Mawar; Ilham Fahmi; Achmad Taufik Ismail (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze strategies for improving the quality of administrative services in building the responsiveness of administrative staff at SMK Al Fudhola Bekasi. This research employed a qualitative approach with a descriptive design. The research subjects consisted of the principal, the head of administration, and students. Data were collected through observation, interviews, and documentation. Data analysis used an interactive model, including data reduction, data display, and conclusion drawing. The results indicate that strategies to improve the quality of administrative services include the implementation of digital-based systems, training for administrative staff, and strengthening leadership roles. The responsiveness of administrative staff is considered fairly good, as indicated by fast, accurate, and responsive services to students' needs. Supporting factors include facilities, leadership support, and staff training, while obstacles include data inconsistencies, lack of communication, and limitations in digital systems. This study concludes that improving the quality of administrative services contributes to enhancing the responsiveness of administrative staff, although further optimization of systems and continuous service management improvements are still required.